Edukasi Kepemimpinan Digital pada Pembelajaran di Sekolah Menengah Kejuruan Abdurrab Pekanbaru - Seri Hartati; Diding Nurdin; Diki Arisandi (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
This non-profit service aims to provide a deeper understanding to SMK Abdurrab Pekanbaru teachers and principals. Digital leadership in learning is a hot topic right now, especially at SMK Abdurrab, where the use of technology in schools is strongly encouraged. The activity will be conducted through educational counseling and comprehension testing for teachers and school leaders on the urgency of digital leadership at Abdullah College. Teachers and of course the principal participated enthusiastically in this activity. This training included pre-test and post-test evaluations. The team/services also conducted a survey on digital leadership. He found that 98% agreed that digital leadership in learning is very important for improving teachers' classroom management skills.